Second and Foreign Language Education 2016
DOI: 10.1007/978-3-319-02323-6_10-1
|View full text |Cite
|
Sign up to set email alerts
|

CLIL: A European Approach to Bilingual Education

Abstract: Content and language integrated learning (CLIL) is a term used especially in Europe for forms of bilingual education where an additional language, in most cases English, is used as the language of instruction in non-language school subjects. This chapter outlines the development of CLIL, embedded both in European level policies and in growing awareness of the new orientations to language learning introduced, for example, in language immersion research. Because of its potential to serve as a context for meaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…The local development of multilingual approaches has led to a variety of small-scale experiments and even educational programmes addressing various students' linguistic backgrounds across diverse social and educational contexts (Barwell et al, 2016;Busch, 2011;Reljić et al, 2015;Sierens and Van Avermaet, 2017). In many EU countries, content and language integrated learning (CLIL), additive language immersion education and bilingual education targeting dominant languages have been set up to promote multilingual learning (Bergroth, 2016;Cenoz et al, 2014;Hélot and Cavalli, 2017;Nikula, 2017). However, they tend to be educational programmes or approaches that caretakers can opt for, and ideally, teachers should have received at least some specialised training for this type of teaching.…”
Section: Identifying Ideological and Implementational Spaces In Itementioning
confidence: 99%
See 1 more Smart Citation
“…The local development of multilingual approaches has led to a variety of small-scale experiments and even educational programmes addressing various students' linguistic backgrounds across diverse social and educational contexts (Barwell et al, 2016;Busch, 2011;Reljić et al, 2015;Sierens and Van Avermaet, 2017). In many EU countries, content and language integrated learning (CLIL), additive language immersion education and bilingual education targeting dominant languages have been set up to promote multilingual learning (Bergroth, 2016;Cenoz et al, 2014;Hélot and Cavalli, 2017;Nikula, 2017). However, they tend to be educational programmes or approaches that caretakers can opt for, and ideally, teachers should have received at least some specialised training for this type of teaching.…”
Section: Identifying Ideological and Implementational Spaces In Itementioning
confidence: 99%
“…Initiatives to promote language programmes aimed at enriching students are gaining importance at the national policy level (Eurydice, 2019;Nikula, 2017). Moreover, such concepts as language awareness (Cenoz et al, 2017;Hélot et al, 2018), pluralistic approaches to languages and cultures (Candelier, 2008) and plurilingual competence (Coste et al, 1997) have gained a foothold in European educational policy discourses, rendering the ideological space visible.…”
Section: Identifying Ideological and Implementational Spaces In Itementioning
confidence: 99%
“…Across European education systems, earlier onset of foreign language learning at school is generally associated with higher proficiency in foreign languages, particularly for writing (European Commission, 2012 [45]). Wilden and Porsch (2016 [46]) found that early onset had a positive impact (mediated by German reading skills) on reading and listening skills in foreign languages for a sample of German students.…”
Section: ) Onset Of Target Language Learning At Schoolmentioning
confidence: 99%
“…Con todo, la enseñanza de idiomas ha ido evolucionando hacia prácticas de enseñanza bilingüe, lo que implica diferencias significativas (Ferreira, 2011): la LE ejerce como vehículo para impartir contenido relacionado con Áreas No Lingüísticas (ANL). Entre otros enfoques, el Aprendizaje Integrado de Contenido y Lengua Extranjera (AICLE) (Coyle, Hood y Marsh, 2010) recibe el mayor reconocimiento en educación bilingüe, sobre todo en Europa (Nikula, 2016). En AICLE, el profesor opta por una integración de LE y contenido, siendo este último el punto de partida de la planificación docente (Meyer, 2010).…”
Section: Introductionunclassified